Wizytacja kościoła parafialnego w Kroszynie w diecezji wileńskiej z 1820 roku - Żurek, Waldemar Witold (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The manuscript of the general visitation in the parish of Kroszyn of 20 November 1820, conducted by the canon of Mińsk, the dean of Nowogródek, the parish priest in Iszkołdź - Rev. Walenty Zan, contains all historical data, personal information and statistics on the parish church and its equipment, church ministry, parishioners, church property, the description of the parish priest’s land and census of the parishioners. Valuable information relates to organizing, by the then parish priest Rev. Magnuszewski, the parish school in 1810 in Kroszyn with the exact description of its students, their age and gender. The parish of Kroszyn also boasted a newly built hospital for the poor. The same text of the general visitation of 1820 was reviewed and signed by the person who conducted the next general visitation in 1825.